Descriptive, injunctive, or the synergy of both? Experimenting normative information on behavioral changes under the COVID-19 pandemic - Okada, Isamu; Yanagi, Itaru; Kubo, Yoshiaki; Kikuchi, Hirokazu (Frontiers in Psychology, 2022)
Backgrounds: The effectiveness of citizens’ behavioral changes to prevent the spread of SARS-Cov-2, such as avoiding large social events, relies on science communication from policymakers and collective action among peer citizens. Extant studies recognize the potential effects of information stimuli on citizens’ behavioral changes, including what epidemiological experts request (injunctive information) and what surrounding people behave (descriptive information). Yet, they have insufficiently assessed the co-occurrence and possible interaction of multiple information stimuli. Methods: 1,819 Japanese citizens aged 18 or over were recruited for an experimental survey during March 1-3, 2021 and asked their views on a hypothetical wedding attendance in Japan while being exposed to randomly assigned normative information stimuli. Their willingness to attend a wedding asked before and after the intervention was measured. Infection risk perception was also asked as a mediating variable. Results: Findings suggest the constant supremacy of descriptive information and no synergistic effects in the interaction of multiple information stimuli. We also report that the effects of injunctive and descriptive information vary according to participants’ risk perception, age, and trust in experts. Conclusion: Our experimental test enables a systematic assessment of multiple normative information and confirms the primacy of descriptive information as the main driver of behavioral change. Communication by medical experts has limitations but is still effective in specific categories of the population.